2021
DOI: 10.3390/beverages7020029
|View full text |Cite
|
Sign up to set email alerts
|

Aroma and Sensory Profiles of Sauvignon Blanc Wines from Commercially Produced Free Run and Pressed Juices

Abstract: Sauvignon blanc is the most important grape cultivar within the New Zealand wine industry, and wines from the Marlborough region are renowned for their intense aromas including tropical, passionfruit, and green capsicum. Quality Sauvignon blanc wines are usually made from free run juice, although press fractions can be included. The chemical aroma composition and sensory profiles of two wine sets made from three press fractions (free run, light press and heavy press) were compared. The compounds 3-mercaptohexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Sauvignon blanc wines produced in Brazil, 23 Slovenia, 24 and Bulgaria contain similar quantities of succinic acid. The shikimic acid concentration in Italian 25 and isopentanol and 2-phenylethanol in New Zealand wines 26 are close to the quantitative data for Bulgarian wines.…”
Section: Resultssupporting
confidence: 78%
“…Sauvignon blanc wines produced in Brazil, 23 Slovenia, 24 and Bulgaria contain similar quantities of succinic acid. The shikimic acid concentration in Italian 25 and isopentanol and 2-phenylethanol in New Zealand wines 26 are close to the quantitative data for Bulgarian wines.…”
Section: Resultssupporting
confidence: 78%
“…In previous studies, the differentiation of wines according to their origin has also been confirmed [27], where other aromatic compounds from the group of volatile thiols and methoxypyrazines, which are also found in the Sauvignon Blanc variety and belong to its primary aromas [27,38], appear. In a future study, quantifying these specific compounds, which are important for the sensory notes of Sauvignon Blanc wine, could shed more light on the differentiation of wines by regions, leading to an in-depth classification based on the chemical composition of the wines.…”
Section: Discussionmentioning
confidence: 68%
“…In previous studies, in the Casablanca area, the sub-area closest to the Pacific Ocean showed a higher acidity [26], which could be comparable to the two valleys much closer to the Pacific Ocean. Additionally, it is important to note that commercially produced wines may have defined styles by each winery, which can impact these parameters, as vinification methods affect the chemical composition of wines [27]. However, for white wines, it is very important and desirable to have higher total acidity [28], making this particularly important for wines from Leyda and San Antonio.…”
Section: Discussionmentioning
confidence: 99%
“…Further volatile compounds are important to the flavors of Sauvignon blanc wines, such as the methoxypyrazines and certain C6 alcohols cis-hexen-1-ol and trans-hexen-1-ol, which can impart grassy, capsicum, and leafy aromas to the wines [65][66][67]. Three methoxypyrazine compounds have been identified in Sauvignon blanc, namely 2-isobutyl-3-methoxypyrazine (IBMP, bell peppers), 2-sec-butyl-3-methoxypyrazine (SBMP, vegetal flavor), and 2-isopropyl-3-methoxypyrazine (IPMP, herbaceous flavor) [68].…”
Section: Sauvignon Blancmentioning
confidence: 99%